2020
DOI: 10.3389/fonc.2020.554388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Genetic, and Prognostic Features of Adrenocortical Tumors in Children: A 10-Year Single-Center Experience

Abstract: Background and Aims: Pediatric adrenocortical tumors (ACTs) are very rare endocrine neoplasms in childhood. In this study, we performed a retrospective analysis of children with ACT treated at our institution by examining clinical and genetic disease features, treatment strategies, and outcomes. Methods: We retrospectively analyzed a cohort of 13 children treated at the Bambino Gesù Children's Hospital from November 2010 to March 2020. Results: The median age at diagnosis was 17 months (range = 0-82 months). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 49 publications
2
37
1
1
Order By: Relevance
“…Information on metastasis was available in 69 reports [ 4 , 7 , 24 , 25 , 27 , 28 , 29 , 32 , 48 , 51 , 52 , 55 , 57 , 59 , 60 , 61 , 63 , 64 , 67 , 68 , 70 , 72 , 73 , 85 , 86 , 89 , 98 , 99 , 101 , 102 , 105 , 106 ]. Among the 2526 patients, at least one metastasis was reported in 632 (25%; 22%—at diagnosis, 3%—at relapse).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on metastasis was available in 69 reports [ 4 , 7 , 24 , 25 , 27 , 28 , 29 , 32 , 48 , 51 , 52 , 55 , 57 , 59 , 60 , 61 , 63 , 64 , 67 , 68 , 70 , 72 , 73 , 85 , 86 , 89 , 98 , 99 , 101 , 102 , 105 , 106 ]. Among the 2526 patients, at least one metastasis was reported in 632 (25%; 22%—at diagnosis, 3%—at relapse).…”
Section: Resultsmentioning
confidence: 99%
“…The classic Weiss criteria [ 113 ], which are well-established in the adult population, are controversial in the pediatric literature. Even though multiple authors have shown that a Weiss score >3 correlates with poor prognosis [ 9 , 26 , 29 , 38 , 54 , 71 , 88 , 94 , 95 , 96 , 97 , 115 , 116 , 117 ] ( Table 5 and Table S4 ), others have shown that Weiss criteria are not applicable in the pediatric population [ 9 , 54 , 64 , 69 , 76 , 77 , 82 , 85 , 88 , 94 , 102 , 116 ] and modifications are necessary, as suggested by Wieneke et al [ 9 ] (see Figure 2 ). There have been several studies validating the reliability of the Wieneke scoring system in both Brazilian and non-Brazilian cohorts of pediatric ACT [ 64 , 70 , 82 ], showing that it is highly predictive of the clinical outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Malignant adrenocortical neoplasms may arise sporadically or can be associated with certain genetic alterations. Common genetic mutations include TP53 tumor suppressor gene and insulin-like growth factor 2 (IGF2) overexpression secondary to 11p15 chromosomal locus mutation [ 3 , 7 , 8 ]. In our case series, we present five cases, three of which occurred in female patients and two in male patients with ages ranging from one to eight years.…”
Section: Discussionmentioning
confidence: 99%